ANALISIS PERHITUNGAN ANGSURAN DAN KEPATUHAN PENYETORAN SERTA PELAPORAN PPH 25 PADA PT. SUMBER INSANI - Najwa Nabila; Azzhara Maya Cessy; Yuni Artika Sari (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study examines the calculation, payment, and reporting of Article 25 Income Tax at PT Sumber Insani. The results show that the calculation and payment comply with regulations, but reporting is still delayed due to administrative constraints..Keywords: Article 25 Income Tax, Tax Compliance..